2012
DOI: 10.1088/0963-0252/21/4/045010
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-dynamic characterization of a radio-frequency induction thermal plasma system for nanoparticle synthesis

Abstract: The fluid flow in a radio-frequency induction thermal plasma (RF-ITP) system for the synthesis of nanoparticles has been characterized using three-and two-dimensional modelling supported by enthalpy probe and calorimetric measurements in order to provide insights for the improvement of the process. The RF-ITP system is composed of a commercial inductively coupled plasma torch mounted on a reaction chamber that is equipped with viewports for diagnostics. The three-dimensional model predicted an almost axisymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Thermal plasmas are high power discharges (from a few to hundred kWs) usually operated at or close to atmospheric pressures, and are demonstrated as effective environments for synthesizing Si‐NPs using both DC and RF sources. Thermal plasmas have electron and gas temperatures exceeding well above 1 eV, enabling processing of nanomaterials with high melting points.…”
Section: Synthesis and Functionalization Of Si‐nps In Plasmasmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal plasmas are high power discharges (from a few to hundred kWs) usually operated at or close to atmospheric pressures, and are demonstrated as effective environments for synthesizing Si‐NPs using both DC and RF sources. Thermal plasmas have electron and gas temperatures exceeding well above 1 eV, enabling processing of nanomaterials with high melting points.…”
Section: Synthesis and Functionalization Of Si‐nps In Plasmasmentioning
confidence: 99%
“…On the other hand, Girshick have reported that in the absence of supersaturated vapor, chemical nucleation plays the key role on the growth of nanoparticles . The group of Colombo have performed a series of studies on the modeling of the formation of Si‐NPs in thermal plasmas . They investigated various mechanisms on Si‐NP formation including fluid dynamics studies, turbulent effects on melting and evaporation of precursor, reactor geometry on the size of synthesized Si‐NPs, all providing deeper insight on nanoparticle growth and formation in thermal plasmas.…”
Section: Synthesis and Functionalization Of Si‐nps In Plasmasmentioning
confidence: 99%
See 1 more Smart Citation
“…The operating pressure has been fixed at 40 kPa. The electromagnetic field equations are solved in an enlarged domain extending 40 mm outside of the torch in the y-direction, using the extended field approach [3]. The coupled power has been set to 10 kW, which corresponds to typical lab-scale generator plate power of 18 kW.…”
Section: Modelling Approachmentioning
confidence: 99%
“…The method has been successfully applied to modelling a wide range of phenomena in thermal plasmas. These include demixing in welding arcs 2 3 , plasma torches 4 , arc plasma reactors 5 6 , and inductively-coupled rf plasmas in gas mixtures 7 8 9 10 , mixing of metal vapour in welding arcs 11 12 13 , mixing of air into plasmas 14 15 16 17 18 19 20 21 22 23 , mixing of polymer vapours into the arc in circuit breakers 24 25 26 27 28 29 , and expansion of metal vapour ablated by a laser into the surrounding air 30 .…”
mentioning
confidence: 99%